Expanding the scope of CRISPR/Cas9‐mediated genome editing in plants using an xCas9 and Cas9‐NG hybrid. Issue 4 (9th January 2020) - Niu, Qingfeng; Wu, Siqun; Li, Yansha; Yang, Xiaoxuan; Liu, Ping; Xu, Yaping; Lang, Zhaobo
Summary: The widely used Streptococcus pyogenes Cas9 (SpCas9) requires NGG as a protospacer adjacent motif (PAM) for genome editing. Although SpCas9 is a powerful genome‐editing tool, its use has been limited on the targetable genomic locus lacking NGG PAM. The SpCas9 variants xCas9 and Cas9‐NG have been developed to recognize NG, GAA, and GAT PAMs in human cells. Here, we show that xCas9 cannot recognize NG PAMs in tomato, and Cas9‐NG can recognize some of our tested NG PAMs in the tomato and Arabidopsis genomes. In addition, we engineered SpCas9 (XNG‐Cas9) based on mutations from both xCas9 and Cas9‐NG, and found that XNG‐Cas9 can efficiently mutagenize endogenous target sites with NG, GAG, GAA, and GAT PAMs in the tomato or Arabidopsis genomes. The PAM compatibility of XNG‐Cas9 is the broadest reported to date among Cas9s (SpCas9 and Cas9‐NG) active in plant. Abstract : In this study, we engineered SpCas9 (XNGCas9) based on mutations from both xCas9 and Cas9‐NG, and found that Cas9‐NG can efficiently mutagenize endogenous target sites with NG, GAG GAA and GAT PAMs in tomato or Arabidopsis genomes. The PAM compatibility of XNG‐Cas9 is the broadest reported to date among Cas9s.